La industria automotriz en México durante las recientes crisis: reorganización productiva y perspectiva geopolítica - Arciniega, Rosa Silvia (2024)
The 2020-2021 global health crisis, the microcomponent shortage emergency from 2021 to current days and the multiple ongoing geopolitical tensions (especially between United States and China) continue to have an impact on the automotive industry. These events have generated disruptions in supply chains, which have highlighted the vulnerabilities of a production system that works Just in Time. In this context, nearshoring has gained significance as a strategy to ensure a resilient and efficient supply chain in terms of times and costs. The objective of this research is to describe the scenario of the automotive industry in Mexico during the recent crisis that have occurred since 2020, and that continue to impact the international trade context identifying nearshoring as a business strategy linked to a productive restructuring, with the aim of managing risks in a complex production network. It is concluded that the post pandemic context demands a reconsideration of the structure and organization of the productive activities of the Mexican automotive industry, with an impact not just at the sectoral level but also at the regional level. Furthermore, the increase in production costs in China also positions Mexico as an attractive trading partner, proposing to launch operations with similar products to the Asian manufacturers. The productive and geographic restructuring, which includes offshoring to reshoring with re-localization of companies and divisions, impose to consider the role that Mexico will play in the changing geopolitical and economic landscape.